An overview of the influencing factors of shooting sports performance - Hu, Y.; Cao, C.; Zhang, K.; Zhang, Y. (Hans, 2020)
The shooting event is the key item for our country to win gold medal in the Olympic Games. For many years, there is rare research on shooting event, which is an important factor restricting the development of shooting event in China. In this study, literature method was used to review the relevant studies on shooting events in recent years, and the factors affecting shooting performance were summarized from the aspects of biomechanics, physiology and psychology. In terms of biomechanics, when choosing a shooting posture, athletes should play at a 15° standing angle rather than traditional postures based on preference. In terms of physiology, low-rate and smooth breathing helps improve the shooter`s athletic performance, but a lot of practice should be carried out for a long time, so that it can be used in the game. In terms of psychology, the coach should de-sign corresponding psychological intervention according to the characteristics of the team members to improve the athlete`s psychological regulation ability, so as to maintain the best competitive state in the game and obtain better results. [Artikel in chinesisch; Abbildungen und Literaturliste englisch]